2021
DOI: 10.1111/wre.12510
|View full text |Cite
|
Sign up to set email alerts
|

Striga gesnerioides (Willd.) Vatke infestation and distribution as affected by soil properties and varieties at the plot and landscape scales in cowpea‐based cropping systems

Abstract: Crop pests, diseases, weeds, limited soil fertility and variable climatic conditions are among the major causes of low agronomic performance and insufficient crop production in the semiarid and subhumid areas of Africa and Asia (Tadele, 2017). Parasitic weeds of the genus Striga have long been recognised as a major biological barrier to crop production, particularly in areas with erratic rainfall that are subject to intensify cropping systems and a reduction in the duration of fallow periods (Parker, 2009). Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Regarding the environment conditions, Striga seeds germination depends on soil fertility, rainfall conditions, and temperature. Kamara et al (2014) and Sadda et al (2018) demonstrated that soil fertility parameters such as sand contents, nitrogen, available phosphorus, organic carbon and pH influence S. gesnerioides infestation level. Mudereri et al (2020) reported that seasonality, temperature and precipitation are the variables most influencing Striga occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the environment conditions, Striga seeds germination depends on soil fertility, rainfall conditions, and temperature. Kamara et al (2014) and Sadda et al (2018) demonstrated that soil fertility parameters such as sand contents, nitrogen, available phosphorus, organic carbon and pH influence S. gesnerioides infestation level. Mudereri et al (2020) reported that seasonality, temperature and precipitation are the variables most influencing Striga occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Mudereri et al (2020) reported that seasonality, temperature and precipitation are the variables most influencing Striga occurrence. Striga seeds need a temperature of around 30° to respond to germination stimulation (Matusova et al, 2004), and soil moisture is a factor controlling Striga occurrence at the landscape scale (Sadda et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Three geomorphological units characterized the study area, namely, lateritic plateaus, sandy hillslopes, and valley bottoms [10]. These landscape sections are primarily associated with farming and animal husbandry, relying predominantly on rainfed crops [11], such as pearl Moench. ], as well as cowpea [Vigna unguiculata subsp.…”
Section: Study Locationsmentioning
confidence: 99%
“…The low water retention capacity of the sandy soils, by default promotes the development of Striga seedbank. Sadda et al (2021) reported 88% probability of the presence of Striga when soil sand fraction is between 65% and 75%.…”
Section: Spatial Analysismentioning
confidence: 99%
“…The narrower range of effect of rainfall on the seedbank indicates that rainfall is a more critical variable influencing Striga seedbank. However, in areas with very sandy soils where soil water holding capacity is low, it is expected that rainfall will have weaker influence than in areas with high clay content Sadda et al (2021). established that the probability of the presence of Striga was as low as 0% when soil moisture level is above 0.045 m 3 m À3 .…”
mentioning
confidence: 99%